Oxford reading tree : level 2 : floppy's phonics : sounds and letters : . Book 10 - Hepplewhite, Debbie; Hunt, Roderick ([S.l.] : Oxford University Press, 2011)
There are 6 books at Level 2: Book 7 practises 'j v w' Book 8 practises 'x y z' Book 9 practises 'zz qu ch' Book 10 practises 'sh th ng' Book 11 practises 'j dge wh' Book 12 practises 'cks tch nk' Each sound is explored through an Oxford Reading Tree scene, first the children should say the sound and trace the letters in the panel, before looking at the key word and picture and saying the sound, there is a list of decodable words for them to read and then they can try to find all words they can that include the focus sound within the picture, some are labelled some are not! Consolidation activities include matching, tracing and reading. There are a total of 42 books in this series from Level 1 to Level 5 (Letters and Sounds Phase 1 to Phase 5)